Painted Church Facades in Byzantine and Post-Byzantine Art and Their Aesthetics - Jevtić, Ivana (Actual Problems of Theory and History of Art, 2019)
Although painted church facades represent long tradition, attested in different regions of the Byzantine world, they have not been recognized as a widespread phenomenon. Scholars, like Slobodan Ćurčić, stressed the necessity to reexamine Byzantine architectural aesthetics in the light of such evidence. Nevertheless, exterior paintings are not yet treated as an integral part of the decorative fabric of buildings. The main problem lies certainly in the scarcity and fragility of the archaeological data that needs to be recordedand collected more systematically.The aim of this article is to draw attention to this issue, most particularly for the Late and Post-Byzantineperiods. It discusses several relevant examples of painted facades, the choice of depicted motives (both ornamental and figurative) and their display on particular parts of the building with intention to question the sources and meanings of that artistic practice. Spurred by the growing interest in non-textual aspects of painted inscriptions, this article reconsiders the place of painted decorations in the adornment of exterior walls and the impact such aesthetic had on the appearance of Byzantine churches and their beholders.
Keywords: Byzantine architecture; church facades; exterior painted decoration; Balkans; Constantinople; Late Byzantine art; Post-Byzantine art